Physical And Mechanical Properties of Acacia mangium and Acacia Auriculiformis from Different Provenances - Sahri, Mohd Hamami; Ashaari, Zaidon; Abdul Kader, Razali; Mohmod, Abdul Latif (Universiti Putra Malaysia Press, 1998)
An assessment of the physical and mechanical properties of Acacia mangium and Acacia auriculiformis from two different provenances, Papua New Guinea and Queensland, Australia were carried out. Three healthy trees of each species were sampled from Indonesia, Malaysia and Thailand. The main objective of the study was to determine the effect of site, species or provenance on the properties of these woods. The tests were carried out in accordance with British Standard BS 373 Standard. The results showed that the specific gravity and the mechanical properties of the samples were affected by the species and provenances. The Indonesian samples exhibited the best results in terms of both physical and mechanical properties compared to the Malaysian and Thailand samples. A. auriculiformis recorded better performance than A. mangium. The results also revealed that the Papua New Guinea provenance was superior for both species.